Distinct motivational effects of contingent and non-contingent rewards - Manohar, S; Finzi, R; Drew, D; Husain, M (Association for Psychological Science, 2017)
When rewards are on offer, we put more energy in, increasing “motivational vigour”. In theory, incentives might drive behaviour for two distinct reasons: first, they increase expected reward; second, they increase the value difference between successful and unsuccessful performance, increasing contingency. Previous studies of motivational vigour never compared these directly. To index vigour, we measured the speed of eye movements towards targets, after participants heard a cue indicating how outcomes would be determined. After cues indicating that monetary reward would be contingent on performance, movements were faster than if reward was random. But even when the cue indicated that reward was guaranteed regardless of speed, movement was still faster than when no reward was available. Contingent motivation generated autonomic arousal, and unlike non-contingent motivation, was effective with penalties as well as rewards. Crucially, motivation by contingent and certain rewards was uncorrelated across individuals, suggesting two separable, independent components of motivation.